Infant Movement Response to Auditory Rhythm. Issue 4 (August 2020) - de l'Etoile, Shannon K.; Bennett, Christopher; Zopluoglu, Cengiz
Rhythmic entrainment occurs when an auditory rhythm drives an internal movement oscillator, thus providing a continuous time reference that improves temporal and spatial movement parameters. Entrainment processes and outcomes are well known for adults, but research is lacking for infants who might benefit from diagnosis and treatment of irregular rhythms within biological, sensorimotor, cognitive, and social domains. The present study used a combination of inertial measurement units and custom-made software to determine the amount, tempo, and regularity of movement in 28 infants aged 6-10 months while they were exposed to silence, an irregular rhythmic cue, or a regular rhythmic cue with tempo changes. We also assessed changes in the infants' movement parameters following a one-week rhythm training protocol. While results revealed no significant effect of auditory condition on amount or tempo of movement, infant movement was significantly more regular when infants were exposed to 120 bpm (beats per minute) than to an irregular rhythmic cue or a 10% faster rhythmic cue (132 bpm). Infants showed no notable changes in movement amount, tempo, or regularity following one week of training involving auditory and physical rhythm. Overall, infants seem to engage in spontaneous movements with or without auditory rhythm but may not show tempo sensitivity through their movements. Increased movement regularity suggests that 120 bpm may be a preferred tempo for infants, at which they are more likely to demonstrate well-timed movements that may reflect interval entrainment. Infants' auditory-motor systems appear not to respond to a 1-week rhythm training protocol.